Reliability analysis of multiphase flow measurements in different oil fields - Ganat, Tarek A.; Hrairi, Meftah; Hawlader, Mohammad Nurul Alam (EID-Energie informationsdients GmbH, 2016)
The significant challenge in the oil and gas industry is the simultaneous measurement of commingled gas, oil, and water streams using separators or multiphase flow meters (MPFM). A major issue when using either test separator or MPFM in oil fields is the uncertainty of the measurements. The aim of this study is to compare three-phase test separator results with MPFM measurements by evaluating field test results from different oil fields in South East Asia, the Middle East, the Mediterranean region, and North Africa for a total of 41 oil wells from different oil fields. Generally, the results show wide variation of the liquid rate measurements between the conventional test separator and MPFM over several periods of time. Such differences, which can be caused by various conditions, become problematic since they impede the accurate estimation of a well’s output and add a degree of uncertainty to any plans to optimize production. A detailed review of each parameter is presented along with its sensitivities when determining the flow rates of oil, gas and water. To date, there are no sets of rules proving the technique for comparison between the test separator and the multiphase flow meter.